Minimally Invasive Approach to Gastrointestinal Tract Duplication Cysts in Children - Ufuk Ates; Farid Khanmammadov; Gulnur Gollu; Kutay Bahadır; Ergun Ergun; Sümeyye Sözduyar; Aydin Yagmurlu; Murat Çakmak; Tanju Aktuğ; Hüseyin Dindar; Meltem Bingöl Koloğlu (Journal of Behçet Uz Children's Hospital, 2020)
INTRODUCTION: Gastrointestinal tract (GIS) duplication cyst is a rare congenital malformation that occur with an incidence of 1 in 4000-5000 live births. Treatment is surgical removal of the lesion, but resection and anastomosis may be required in case of lumen associated cyst. In this study, it was aimed to investigate the role of minimally invasive approaches in GIS duplications. METHODS: This study included nine children who underwent surgery due to GIS duplication in our clinic between the years 2009 – 2018. Demographic data, diagnostic tools, duplication location, surgical approach, operation time and complications were reviewed retrospectively. RESULTS: Nine children were included in the study, four of them were male, five were female. The mean age was 26 months (1-71 months). Seven children underwent GIS duplication cyst excision without intestinal resection. The mean duration of surgery was 89 minutes (55 min-110 min). The mean of hospital stay was five days(1-11 days). DISCUSSION AND CONCLUSION: Minimally invasive approaches for GIS duplication in children are safe and easy procedures. The laparoscopic approach is a convenient method to confirm the diagnosis and localization of the cyst.